Gatherer ancestry associated with national happiness - Matthew Frederick Basilico (PLoS ONE, 2026)
Efforts to improve human emotional wellbeing through economic growth have seen varied success. One interpretation of the lack of wellbeing returns to economic growth is that humans may have been more emotionally suited to patterns of life in pre-agricultural societies. This study examines the hypothesis, dating to Rousseau, that descendants of hunter-gatherer societies have higher levels of subjective wellbeing. It utilizes data from 1265 small scale societies in the Murdock Ethnographic Atlas to construct a country-level measure of gatherer ancestry. Average country-level happiness and life satisfaction were derived from the World Values Survey which covered 104 countries from 1981–2014. Gatherer ancestry was significantly associated with happiness, controlling for contemporary income per capita (beta = 13.58; standard error = 3.0, R 2 = 11.8%, p < 0.01). Results were robust to an extensive list of historical and contemporary controls. The findings are consistent with the hypothesis that gatherer lifestyle organization may hold insights for human emotional wellbeing.